Activities Contributing to Total Energy Expenditure in the United States: Results from the NHAPS Study - Block Gladys; Dong Linda; Mandel Shelly (BMC, 2004)
Abstract Background Physical activity is increasingly recognized as an important factor influencing health and disease status. Total energy expenditure, both low-intensity and high-intensity, contributes to maintenance of healthy body weight. This paper presents the results of a quantitative approach to determining the activities that contribute to total energy expenditure in the United States. Methods Data from the National Human Activity Pattern Survey (NHAPS) were used. In 1992-1994 the NHAPS sampled 4,185 females and 3,330 males, aged 18 years and over, weighted to be representative of the 48 contiguous United States. A detailed report of each activity performed in the previous 24 hours was obtained. A score was created for each activity, by multiplying duration and intensity for each individual and summing across individuals. This score was then used to rank each activity according to its contribution to total population energy expenditure, for the total sample and separately for each gender, race, age, region, and season. Results This analysis reveals our society to be primarily sedentary; leisure time physical activity contributed only approximately 5% of the population's total energy expenditure. Not counting sleeping, the largest contributor to energy expenditure was "Driving a car", followed by "Office work" and "Watching TV". Household activities accounted for 20.1% and 33.3% of energy expenditure for males and females respectively. Conclusion The information presented in this paper may be useful in identifying common activities that could be appropriate targets for behavioral interventions to increase physical activity.